Getting a lift: The impact of aerial cable cars in La Paz, Bolivia - Sebastian Martinez; Raul Sanchez; Patricia Ya\~nez-Pagans (Inter-American Development Bank (IDB), 2018)
This paper studies the effects of areal cable cars on mode of transport, time use and employment in the metropolitan area of La Paz, Bolivia. Using an instrumental variables approach, we estimate local average treatment effects of cable car use for residents who use the system due to proximity to a cable car station. Results suggest that cable-car users substitute private transport in favor of public transit and experience large savings in commute time, which is reallocated toward educational and recreational activities. Users also increase self-employment activities, potentially reflecting improved access to local labor markets. The positive effects of the cable-car are driven by residents of the city of El Alto, a city with high concentration of poor and indigenous households on the high plateau bordering La Paz. The economic benefits of the cable car outweigh costs by a ratio of 1.05 to 2.16.
Keywords: L92; O18; R41; 330; Cable Car; Mi Teleférico; Mass Transit; Travel Time; Employment